MINIMIZE DOWN-TIME AFTER BLACK-OUT IN THE ELECTRICAL POWER SYSTEM OF PT.PUNCAKJAYA POWER - WIDADA (NIM : 29109145); Dosen Pembimbing: Dr. Ir. Mursyid Hasan Basri, HADI
As a leading provider of electrical services, PT.Puncakjaya Power (PT.PJP) very concern and priority to three main aspects of the electrical operating system of power quality (power quality), economic dispatch and reliability (reliability) in supplying electric power system for PT.Freeport Indonesia (PTFI) as a single customer. The combination of Steam Power Plant with the Diesel Power Plant need a high system reliability and plant composition settings (mix -generation) to produce the best power quality and generate best economic value for the customer and company. Disruption that could result in failure or miss operation on consumer equipment must be overcome with an appropriate and rapid recovery system and procedure. The methodology used to analyze this problem is using Six Sigma DMAIC (Define-Measure-Analyze-Improve-Control) to identify and analyze problems to find the roots of the problem so it may be possible remedial measures. The tools used in the analysis is Fishbone (Ishikawa) diagrams, Process diagrams, SIPOC (Suppliers-Inputs-Process-Outputs-Customers) and Matrix Diagrams XY. The roots of the problems that arise at every stage of the recovery process can be grouped into three categories as the root causes that can be controlled (C), the root causes that arise from the operation procedure, safety procedure, corporate regulation, as well as standard operation procedure recommended by the manufacturer (P) and the root causes that difficult or cannot be controlled or noise (N). By doing a weighting towards the roots of these problems, some major problems that became the root cause of the late recovery process will be achieved. Then do the analysis on the major roots cause to confirm with the alternative solutions that to be possibly implemented at this time. Three alternative solutions of integration between the engine monitoring automation system with the load shedding and load recovery system (EMAS-LSLR), the addition of black start generator capacity in portsite DWP plant, and installation of Static Var Compensator (SVC) or STATCOM on the high voltage transmission network are capable to provide a significant acceleration of recovery processes. Integration of EMAS-LSLR is the most profitable alternative to the B / C ratio of 7.54 and increasing speed of the process of around 40%. With the budget required is about U.S. $ 255.64K, the potential savings amounted to U.S. $ 1.9M each time the blackout or the equivalent of U.S. $ 12.0M per year. This value depends of course also with the standard operating procedures in place to minimize the parameters that cannot be measured.